Serviҫo Nacional Inteligência; Hambatan, Tantangan, dan Implikasinya Terhadap Keamanan Nasional di Timor Leste - Jon Martins Ximenes (Al-Adalah: Jurnal Hukum dan Politik Islam, 2021)
This research is a strategy to improve the performance of National Serviço Intelligence (SNI) in carrying out national security in Timor Leste. The influence of globalization that is increasingly felt throughout the world today has prompted some people to question the existence of the National Intelligence Service (SNI) in facing internal and external threats with professionals. The research method used in this research is descriptive qualitative data collection, namely interviews, observations, group discussions and documentation. The conclusion of this research is that Serviço Nacional Intelligence (SNI) plays a role in producing information that contributes to maintaining national independence, national interests and external security, as well as ensuring internal security in preventing sabotage, terrorism, espionage and organized crime. However, the low quality of human resources, lack of budget, and limited facilities and infrastructure are obstacles and challenges for the Serviço Nacional Intelligence (SNI) in maximizing it as a government information agency.